The transcriptional transactivator of human foamy virus maps to the bel 1 genomic region. - Rethwilm, A (1991)
The human foamy virus (HFV) genome possesses three open reading frames (bel 1, 2, and 3) located between env and the 3' long terminal repeat. By analogy to other human retroviruses this region was selected as the most likely candidate to encode the viral transactivator. Results presented here confirmed this and showed further that a deletion introduced only into the bel 1 open reading frame of a plasmid derived from an infectious molecular clone of HFV abolished transactivation. In contrast, deletions in bel 2 and bel 3 had only minor effects on the ability to transactivate. The role of the bel 1 genomic region as a transactivator was further investigated by eukaryotic expression of a genome fragment of HFV spanning the bel 1 open reading frame. A construct expressing bel 1 under control of a heterologous promoter was found to transactivate the HFV long terminal repeat in a dose-dependent fashion. Furthermore, it is shown that the U3 region of the HFV long terminal repeat is sufficient to respond to the HFV transactivator.